Boy21 - Quick, Matthew 1973- (Little, Brown and Company, 2013)
Finley, an unnaturally quiet boy who is the only white player on his high school's varsity basketball team, lives in a dismal Pennsylvania town that is ruled by the Irish mob. When his coach asks him to mentor a troubled African American student who has transferred there from an elite private school in California, he finds that they have a lot in common in spite of their apparent differences
Keywords: Emotional problems of teenagers / Juvenile fiction; Irish Americans / Juvenile fiction; Gangsters / Juvenile fiction; High schools / Juvenile fiction; Violence / Juvenile fiction; Basketball stories; Friendship / Juvenile fiction; African Americans / Juvenile fiction; Pennsylvania / Juvenile fiction; Emotional problems / Fiction; African Americans; Emotional problems of teenagers; Friendship; Gangsters; High schools; Irish Americans; Violence; Pennsylvania; African Americans / Fiction; Friendship / Fiction; Gangs / Fiction; Irish Americans / Fiction; Violence / Fiction; High schools / Fiction; Basketball / Fiction; Pennsylvania / Fiction; Fiction; Juvenile works; Young adult; Jugendbuch